2020
DOI: 10.36483/vanvetj.651515
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalus Trichamygdalus (Tatlı Badem) ve Amygdalus nana L. (Acı Badem) Bitkilerinin Antimikrobiyal Etkisinin Araştırılması

Abstract: In this study, the antimicrobial effect of bitter almond (Amygdalus nana L.) and sweet almond (Amygdalus trichamygdalus) extract were investigated. The extracts of the sweet almond which plants collected from Diyarbakır Ergani district and the extracts of the bitter almond which plants collected from Van Tuşba district. The almonds dissolved in deionized water, alcohol, and ether. Fungus, gram positive and gram negative bacteria were used as pathogens in this study. The effects of the extracts on pathogens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…& Huet var. grandiflorum has antimicrobial effects >5 mg/ml against E. coli ATCC25922, 0.625 mg/ml against S. aureus ATCC29213 and >5 mg/ml against C. albicans ATCC10231; ethanol extract against the same microorganisms showed antimicrobial effects >5 mg/ml, 5 mg/ml and 1.25 mg/ml, respectively (Saraç et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…& Huet var. grandiflorum has antimicrobial effects >5 mg/ml against E. coli ATCC25922, 0.625 mg/ml against S. aureus ATCC29213 and >5 mg/ml against C. albicans ATCC10231; ethanol extract against the same microorganisms showed antimicrobial effects >5 mg/ml, 5 mg/ml and 1.25 mg/ml, respectively (Saraç et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…Some studies showed that plants can be successful in overcoming antibiotic resistance with combinatorial approaches (Van Vuuren & Viljoen, 2011;Hutchings & Cock, 2018;Blonk & Cock, 2019). Today, 80% of the active substances used in the treatment of infectious diseases are thought to be vegetable-oriented (Özdek, Seçkin, & Çibuk, 2020). Therefore, the use of plant extracts as an antioxidant and antimicrobial agent has been expanded in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 hours, the solution was filtered and then both filtered solutions were mixed together and then evaporated repeatedly by rotary evaporator at 50 °C and 70 rpm. 5.7% w/w dry extract were obtained from Concentrated extract by lyophilizing and stored at -20 °C (Özdek Seçkin et al, 2020).…”
Section: Preparation Of the Extractmentioning
confidence: 99%
“…The inability to control infections due to antibiotic resistance may cause an increase in patient deaths as well as an increase in healthcare costs (Moodley et al 2020). The antimicrobial properties of plants and nanoparticles derived from plants have been recently investigated (Ozdek et al 2020;Subramanyam et al 2021). For this reason, in this study, AgNPs and ZnNPs green nanoparticles from Nasturtium officinale were synthesized and their antimicrobial effects were investigated.…”
Section: Introductionmentioning
confidence: 99%